The Content Analysis of Grammar Activities in 'Wider World 2' Student"™s Book by Pearson for Grade Seven Students - Juniar, Rima (Proceedings International Conference on Teaching and Education (ICoTE), 2024)
The objective of this study is to use Bloom's revised taxonomy to analyze the context of the grammar activities in Wider World 2 Student"™s Book. To achieve the research goal, a content analysis was performed. The researcher analyzed the textbook based on Bloom's revised taxonomy. According to the data, the textbook has dominant grammar activities, particularly on the cognitive process of "understand" and "remember" with 47% and 32% out of 189 grammar activities. Moreover, the data shows that the grammar activities in the textbook have an uneven distribution of higher and lower cognitive processes. There is a vast lower thinking skills percentage since most grammar activities focus on the "understand" aspect. While the second dominant aspect is "remember" which includes lower thinking skills. Therefore, Wider World 2 Students"™ Book highlights Bloom"™s revised taxonomy"™s lower cognitive thinking process, represented by the "understand" and "remember" thinking processes.